Magnetic field assisted fabrication of yolk–shell Co3V2O8 microspheres for superior lithium-ion storage. (27th March 2023) - Zhou, Jiafeng; Bai, Jin; Mao, Yunjie; Ma, Hongyang; Zhu, Xuebin; Zhao, Bangchuan; Sun, Yuping
Abstract : The yolk–shell Co3 V2 O8 microspheres fabricated via the magneto-solvothermal method show a high specific capacity, outstanding rate performance, and long cycling life. Abstract : Yolk–shell Co3 V2 O8 microspheres with abundant mesopores are fabricated via the magneto-solvothermal method under 1 T magnetic field followed by a proper heat-treatment process. The applied magnetic field in the solvothermal process can reduce the surface energy of the spheres and make the Co3 V2 O8 particles at the sphere surface grows more easily, resulting in the formation of the yolk–shell architecture. The unique structure makes the material possess a higher surface area, more sufficient void space, and shorter ion/electron transport distance, which facilitates charge transfer and accommodates the volume change of the materials during the charge/discharge process, leading to an excellent lithium-ion storage performance. The Co3 V2 O8 microsphere electrode can deliver a high capacity of 1233.5 mA h g −1 after 100 cycles at 0.5 A g −1 . As the current density increases to 8 A g −1, the specific capacity of the Co3 V2 O8 yolk–shell microspheres can also maintain a high value of 665.4 mA h g −1 .